2010
DOI: 10.1530/eje-10-0627
|View full text |Cite
|
Sign up to set email alerts
|

Minimal changes in environmental temperature result in a significant increase in energy expenditure and changes in the hormonal homeostasis in healthy adults

Abstract: Objective Resting energy expenditure (EE) is a major contributor to the total EE and thus plays an important role in body weight regulation. Adaptive thermogenesis is a major component of EE in rodents, but little is known on the effects of exposure of humans to mild and sustainable reduction in environmental temperature. Design To characterize the dynamic changes in continuously measured resting EE, substrate utilization, and hormonal axes simultaneously in response to mild reduction in environmental temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
71
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 34 publications
8
71
2
1
Order By: Relevance
“…In addition to glucose, cold exposure had no significant effect on plasma insulin, thyroid hormones, or even epinephrine, demonstrating that there was not a generalized activation of the classic response to stressors (23). The cold-associated increase in C-peptide without changes in glucose reflects a state of relative insulin resistance that may have been caused by elevated norepinephrine, as previously described (24). The elevated lactic acid levels were likely a result of glycolysis and amino acid metabolism in the BAT itself (18,25) and possibly also from subclinical, low-grade muscle contraction.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to glucose, cold exposure had no significant effect on plasma insulin, thyroid hormones, or even epinephrine, demonstrating that there was not a generalized activation of the classic response to stressors (23). The cold-associated increase in C-peptide without changes in glucose reflects a state of relative insulin resistance that may have been caused by elevated norepinephrine, as previously described (24). The elevated lactic acid levels were likely a result of glycolysis and amino acid metabolism in the BAT itself (18,25) and possibly also from subclinical, low-grade muscle contraction.…”
Section: Discussionsupporting
confidence: 58%
“…jci.org Volume 126 Number 9 September 2016 in future studies of other important β 1 AR-mediated processes, such as cardiac function, smooth muscle tone, the hypoglycemia counterregulatory response, and adipose tissue physiology. Also, given our findings in calorie-restricted GC-β 1 AR -/-mice, we would predict that other conditions associated with enhanced sympathetic drive, such as psychosocial stress and cold exposure -both of which have been shown to be associated with increased plasma ghrelin levels -may involve robust β 1 AR-dependent ghrelin secretion responses (50,(84)(85)(86)(87) on which the full physiological responses to those conditions may depend. Furthermore, the occurrence of hypoglycemia in calorie-restricted GC-β 1 AR -/-mice and the prevention thereof by ghrelin administration suggest that closer blood glucose monitoring might be prudent in cachectic individuals if beta blocker therapy becomes indicated, just as has already been recommended for children with infantile hemangioma treated with propranolol, for whom we now propose that reduced ghrelin secretion contributes to the beta blocker-associated hypoglycemia.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] Based on findings from studies involving animals and humans, the effects of brown adipose tissue activation extend beyond thermogenesis, by influencing whole-body metabolism and possibly overall body weight. [7][8][9][10][11][12][13][14][15][16][17][18] Small intervention trials involving humans have suggested that even mild exposure to ambient cold -such as lowering a thermostat from 24°C to 19°C -can increase activity of brown adipose tissue by 30%-40%, resulting in substantial improvements in insulin sensitivity. [15][16][17][18] In theory, greater insulin sensitivity should improve glucose handling, but whole-population studies evaluating the potential for cold exposure to reduce glucose mishandling are lacking.…”
mentioning
confidence: 99%